Normal endothelial but impaired arterial development in MAP-Kinase activated protein kinase 2 (MK2) deficient mice. Issue 1 (December 2016) - Napp, L.; Jabs, Olga; Höckelmann, Anna; Dutzmann, Jochen; Kapopara, Piyushkumar; Sedding, Daniel; Gaestel, Matthias; Bauersachs, Johann; Bavendiek, Udo
Abstract Angiogenesis is a fundamental process during development and disease, and many details of the underlying molecular and cellular mechanisms are incompletely understood. Mitogen-activated protein kinase (MAPK)-activated protein kinase 2 (MK2), a major downstream target of p38 MAPK, has recently been identified as a regulator of Interleukin 1β dependent angiogenesis in vivo, and in vitro data suggest a role of MK2 for VEGF-dependent angiogenic processes in endothelial cells. We thus hypothesized that MK2 plays a role during physiological vascular development in vivo. Vascular development was investigated in the retina of MK2-deficient mice. Retinal angiogenesis such as sprouting, branching and pruning was unchanged in MK2-/- mice compared to wildtype littermates. Early arterial development was also comparable between genotypes. However, with further expansion of vascular smooth muscle cells (SMC) during maturation of the arterial network at later time points, the number of arterial branch points was significantly lower in MK2-/- mice, resulting in a reduced total arterial area in adult mice. Isolated aortic smooth muscle cells from MK2-/- mice showed a more dedifferentiated phenotype in vitro and downregulation of central SMC marker genes, consistent with the known impaired migration of MK2-/- SMC. In conclusion, MK2 is not required for physiological retinal angiogenesis. However, its loss is associated with an altered genetic profile of SMC and an impaired arterial network in adult mice, indicating a distinct and probably cell-specific role of MK2 in arteries.